Os pescadores artesanais profissionais de Porto Rico, Estado do Paraná, Brasil : turismo e identidade. - Paiola, Lucy Mara (2009)
Professional artisan fishermen in Porto Rico-PR with their forms of appropriation of the environment based on the principles of the traditional culture are threatened by the risk of having the continuity of such living rendered unviable, and of the disappearance of their so cherished life style. Parallel to those processes, another one has occurred, tourism. The aim of this study was to investigate possible involvement of the mentioned group of professional artisan fishermen in those touristic activities and possible implication of such development in their life and identity. From February 2 to 14, 2008, twenty-two fishermen and four former ones, which have not completely quit fishing, we polled. The obtained conclusions show the fishermen have been engaging in such activities, but this involvement, as stated by them, has only given opportunity to a relative maintenance of some of their cultural values and a life style close to nature.